2020
DOI: 10.3389/fgene.2020.568192
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Nine-RNA Binding Protein Signature Predicting Overall Survival for Kidney Renal Clear Cell Carcinoma

Abstract: Cumulative studies have shown that RNA binding proteins (RBPs) play an important role in numerous malignant tumors and are related to the occurrence and progression of tumors. However, the role of RBPs in kidney renal clear cell carcinoma (KIRC) is not fully understood. In this study, we first downloaded gene expression data and corresponding clinical information of KIRC from the Cancer Genome Atlas (TCGA) database, International Cancer Genome Consortium (ICGC), and Gene Expression Omnibus (GEO) database, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Although the expression of EXOSC5 has been studied in different cancers, there are limited reports about the clinical relevance and functional roles of EXOSC5 in solid tumors. Compared to normal tissues, increased expression of EXOSC5 was reported in many types of tumor cell lines, such as hematopoietic tumor, cervical carcinoma, melanoma, colon cancer cell and renal cell carcinoma [11,18]. Yang et al purified recombinant EXOSC5 monoclonal antibody and found specific serological responses in 10-33% of patients with melanoma, lung cancer and prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although the expression of EXOSC5 has been studied in different cancers, there are limited reports about the clinical relevance and functional roles of EXOSC5 in solid tumors. Compared to normal tissues, increased expression of EXOSC5 was reported in many types of tumor cell lines, such as hematopoietic tumor, cervical carcinoma, melanoma, colon cancer cell and renal cell carcinoma [11,18]. Yang et al purified recombinant EXOSC5 monoclonal antibody and found specific serological responses in 10-33% of patients with melanoma, lung cancer and prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, compared with other similar research, our hypoxia-immune-related prognostic model had better effectiveness. Zhong et al developed a prognostic model based on nine RNA-binding protein signatures, and the AUC values of this model were 0.71, 0.66, and 0.69, respectively, for 1-, 3-, and 5-year OS (Zhong et al, 2020). Xu et al constructed a prognostic risk model based on PPAR pathway-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…Zhong et al . developed a prognostic model based on nine RNA-binding protein signatures, and the AUC values of this model were 0.71, 0.66, and 0.69, respectively, for 1-, 3-, and 5-year OS ( Zhong et al, 2020 ). Xu et al .…”
Section: Discussionmentioning
confidence: 99%
“…RPL13 was highly expressed in gastrointestinal cancer and enhanced the proliferation of gastrointestinal cancer cells and may be a useful molecular marker of drug efficacy in gastrointestinal cancer (46). In kidney renal clear cell carcinoma (KRCCC), researchers found that RPL13 was associated with the prognosis of tumor patients (47). Huang found that RPL14 are frequently altered during tumorigenesis of esophageal squamous cell carcinomas (ESCC) and could be used for the early detection of ESCC (48).…”
Section: Discussionmentioning
confidence: 99%